(untitled) - Asahi, Isoshi (Tokyo, 1939)
The present book is intended as a rough sketch of the main changes that took place in Japanese trade and industry during the period 1930 -1939, with special emphasis on the conditions brought about by the present China Affair.
Keywords: Industries,Công nghiệp; Japan,Nhật Bản